Evaluation of applicability of Pont's index in Serbian population - Filipović Gordana; Radojičić Julija; Igić Marija; Stojanović Nikola; Đorđević Nadica (Medicinski fakultet i Klinika za stomatologiju, Niš, 2019)
Introduction: The applicability of Pont's Index to orthodontic patients may guide clinicians in predicting an ideal arch width, necessary to accommodate the dentition, unloose crowding and to produce more stable final results. The aim: of this study was to establish the applicability of Pont's Index to Serbian population and compare the results with those acquired from studies conducted on different ethnic subjects. Materials and methods: Dental casts of 200 Serbian subjects (100 males and 100 females) were used in this study. All subjects had normal Class I occlusion, with no history of orthodontic treatment. Measurements were taken by a digital caliper (precision of 0.01 mm). The mesiodistal widths of the maxillary permanent incisors, as well as interpremolar and intermolar maxillary arch widths, were measured. Using t-test Pont's Index ratios between this study and Pont's study and between genders were compared. Pearson correlation coefficients between measured and arch width values according to Pont's formulae were determined. Results: Although correlations determined between the calculated arch width and corresponding values calculated using Pont's Index were high in all cases for both genders, a statistically significant difference was observed (p<0.001). Calculated Pearson coefficient between real and measured arch width are found to be high and statistically significant. Conclusion: Our results suggest that the Pont's Index was not applicable to Serbian population and specific standards for this population might be needed.